Feast with the People of the South Wind: An Ethnobotanical Approach to Kanza Subsistence Patterns, 1724-1873 - Fluker, Morgan (Kansas State University, The Chapman Center for Rural Studies, 2017)
A presentation of the information gathered regarding the Kanza Indian tribe of northeastern Kansas. The information pertains to the tribe’s dietary practices, specifically those that utilized the wild and native resources surrounding their villages. As time passed and the location of their villages changed, it is assumed that the resources they had access to would change. This study will show that this was not necessarily the case. The Kanza people were knowledgeable of their environment and chose new village locations that suited their lifestyle. The natural resources found around each village, dating from 1724-1873, are listed chronologically to show the consistencies and changes between the villages, followed by and evaluation of the uses of each resource as an attempt to show how important the resources were in the shaping of their lifestyle.
Morgan Fluker, “Feast with the People of the South Wind: An Ethnobotanical Approach to Kanza Subsistence Patterns, 1724-1873,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/252.
Keywords: American Indians; Kaw; Kanza; Kaw Indians; Kansa Indians; Ethnobotany